Prevalence of depression and its associations with cardio-metabolic control in Aboriginal and Anglo-Celt patients with type 2 diabetes: The Fremantle Diabetes Study Phase II. Issue 3 (March 2015) - Davis, Timothy M.E.; Hunt, Kerry; Bruce, David G.; Starkstein, Sergio; Skinner, Timothy; McAullay, Daniel; Davis, Wendy A.
Highlights We assessed depression in Australian Aboriginal and Anglo-Celt patients with type 2 diabetes. Depression was more than twice as prevalent in the Aboriginal group. This difference was no longer evident after adjustment for confounders, but there was still more major and untreated depression amongst Aboriginals. Depression was associated with adverse cardiovascular risk factors.